Proposal for the creation of an Observatory of Intangible Cultural Heritage and Museums in Peru - Jaureguy Robinson, Claire (2025)
This article sets out the proposal to establish an Observatory for Intangible Cultural Heritage and Museums of Peru, conceived as a space for research, coordination, and cultural management. It also reflects on the historical processes of heritage-making and the challenge of ensuring the safeguarding of intangible cultural heritage. The Observatory seeks to integrate digital tools for inventory creation, data analysis, and innovation, with a territorial approach that positions regional museums as nodes of citizen participation and decentralization. It is envisaged as a platform capable of systematizing information, generating cultural indicators, and fostering community participation in heritage safeguarding.